Teachers' practice in developing visually impaired learners' reading skills in the junior primary phase in northern Namibia - Nuugonya, Elizabeth Nangula (Rhodes University, Faculty of Education, Department of Education)
Namibia has adopted, ratified and followed several international policies on disability and inclusive education including the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD). Since 2014, the Namibian education system has been working towards the implementation of the Sector Policy on Inclusive Education to promote an education system that is accessible, inclusive, equitable and of good quality (Namibia. Ministry of Education, Arts and Culture: Sector Policy on Inclusive Education, 2013). The policy aims to address barriers faced by learners with disabilities and how teachers develop ways of teaching that respond to the individual differences. Reading in a second language tends to develop more slowly by visually impaired learners, although the Junior Primary Phase syllabus promotes equal opportunity for all learners to participate in reading equally irrespective of learners' disabilities. Teachers should understand how to teach and accommodate learners who are visually impaired and all reading materials should be fit for purpose and support these learners appropriately. Thus, this study explores how Junior Primary teachers develop visually impaired learners' reading skills to provide accessible education to them. Learning to read is challenging for most learners, but even more for learners who are visually impaired. Learning to read braille is a complex process, far more than reading print texts. This study seeks to examine how learners are taught to read using braille in a school for visually impaired learners in Namibia, Oshana region. The motivation for this research study was twofold - firstly, my interest in the development of reading skills with visually impaired learners was aroused by my teaching experience. Secondly, due to my realisation that the area was under-researched in Namibia; I wanted to fill the existing gap in the development of reading skills in braille and print. The study critically engaged teachers to help me obtain an understanding of how they develop reading instructions with visually impaired learners and the factors that enabled the development of braille literacy and the challenges that hampered the development of reading skills. The study took the qualitative case study approach underpinned by an interpretivist orientation. Data was collected using semi-structured observation during reading lessons and focus group interviews. The Theory of Practice Architectures (ToPA) was used as a lens to analyse the promoting and constraining factors in teaching visually impaired learners reading skills. The study found that teachers used different reading methods to promote the development of reading skills such as reading aloud, tactile methods and phonics. The study further noted that teachers mostly created their own reading materials due to the lack of reading materials and reading books printed in braille. Although learners were supported during reading, the challenge of developing reading skills with visually impaired learners remains a challenge. I hope that the findings from this research study strengthen the development of reading skills in all special schools and contribute to the creation of knowledge on the development of reading skills with visually impaired learners in Namibia. As a means to further support learners who experience visual impairments, this study recommends that more formative research studies on the notion of teachers' practice in developing reading skills with visually impaired learners should be conducted to bring about change.
Keywords: Children with visual disabilities Education-- Namibia Oshana; Reading (Elementary)-- Namibia Oshana; Inclusive education-- Namibia Oshana; Convention on the Rights of Persons with Disabilities and Optional Protocol (2007 March 30); Braille-- Study and teaching (Elementary)-- Namibia Oshana; Teachers of the blind-- Namibia Oshana